THE ENERGY OF AN INTELLECT AS A MANIFESTATION OF GIFTEDNESS - Vasyl Kremen (National Academy of Educational Sciences of Ukraine, 2018)
Throughout the years of independence in the spiritual culture, the line for the absolutisation of the national ethos as the determining factor of social life was conducted. In the education system meritocratic tendencies began to appear bright enough, which correlate with similar trends within the framework of the development of the whole society. However, there is not only the "energy of the nation", but also the energy of the intellect. The emphasis on the role of the national cannot be constructive and scientific, unless we take into account the important, and in many cases the determining role of the intellect, the effectiveness of the mind. It is the intellect, not the ethnic or any other identity that creates new technologies, makes breakthroughs in science, and makes projects for the continued existence of man. Formation of the elite is the result of the selection by society of its most valuable representatives based on the manifestation of their individual endowments. In the context of considering the formation of the intellectual elite in the context of globalization, it is important to consider the formation of a new type of educational space, which expands the possibilities for the formation and development of the intellectual elite based on the manifestation of a person's giftedness. As a result, the processes of designing elite groups in the context of globalization acquire their specifics, and the problems of the formation of the intellectual elite are maximally manifested at the institutional level. As a result, now we can talk about a complex of tendencies in the development of the education system that allow it to actively participate in the process of forming the intellectual elite of society and develop its intellectual capital.